Applying the model of diffusion of innovations to understand facilitators for the implementation of maternal and neonatal health programmes in rural Uganda - Paina, Ligia; Namazzi, Gertrude; Tetui, Moses; Mayora, Chrispus; Muhumuza Kananura, Rornald; Kiwanuka, Suzanne N.; Waiswa, Peter; Mutebi, Aloysius; Ekirapa-Kiracho, Elizabeth (Globalization and health, 2019)
In Uganda, more than 336 out of every 100,000 women die annually during childbirth. Pregnant women, particularly in rural areas, often lack the financial resources and means to access health facilities in a timely manner for quality antenatal, delivery, and post-natal services. For nearly the past decade, the Makerere University School of Public Health researchers, through various projects, have been spearheading innovative interventions, embedded in implementation research, to reduce barriers to access to care. In this paper, we describe two of projects that were initially conceived to tackle the financial barriers to access to care – through a voucher program in the community - on the demand side - and a series of health systems strengthening activities at the district and facility level - on the supply side. Over time, the projects diverged in the content of the intervention and the modality in which they were implemented, providing an opportunity for reflection on innovation and scaling up. In this short report, we used an adaptation of Greenhalgh’s Model of Diffusion to reflect on these projects’ approaches to implementing innovative interventions, with the ultimate goal of reducing maternal and neonatal mortality in rural Uganda. We found that the adapted model of diffusion of innovations facilitated the emergence of insights on barriers and facilitators to the implementation of health systems interventions. Health systems research projects would benefit from analyses beyond the implementation period, in order to better understand how adoption and diffusion happen, or not, over time, after the external catalyst departs.
Keywords: Uganda; Innovation; Maternal health; Health systems research; Vouchers; Diffusion